Simulação e análise numérica de equações diferenciais estocásticas unidimensionais: uma abordagem introdutória - Felipe Carvalho Alvares da Silva (2013)
This work presents an introductory discussion with respect to numerical methods for the simulation of stochastic differential equations. We begin with the presentation of essential mathematical concepts about probability and stochastic processes. In the following, we present the classical discretization schemes and make a theoretical and a experimental analysis about the behavior of these methods. At the end we present an algorithm that explores the method of rejection to generate an exact solution of a class of stochastic differential equations.